2015
DOI: 10.14421/biomedich.2015.41.17-24
|View full text |Cite
|
Sign up to set email alerts
|

Krokot Extract (Portulaca Oleracea. L) as Natural Light-harvesting pigments for Dye-Sensitized Solar Cells (DSSCs) : Influence of Dye Acidity

Abstract: Dye-sensitized solar cells (DSSCs) was fabricated using natural dyes extracted from krokot (Portulaca Oleracea. L). The effect of dye acidity was investigated on natural pH extract, 5.00, 4.00 and 3.00 of pH. The efficiency and stability DSSCs as a function of the dye acidity was studied. The result of the UV-Vis shows that the absorption of wave-length from dye extract of krokot is located in the visible region with the absorbance peak in 410.5 nm and 664.5 nm which are the peak of chlorophyll. The efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…The OP1 and OP2 samples are rich in these pigments due to the presence of purslane in their composition. This agrees with other investigations which mentioned that purslane has an elevated content of alpha and beta chlorophylls (Nurfaizah et al, 2015). Our results showed that foliage from OP1 samples is a good source of photosynthetic pigments; in addition, the proportion of carotenoids that OP1 contains are similar to other food supplements.…”
Section: Antioxidant Compoundssupporting
confidence: 92%
“…The OP1 and OP2 samples are rich in these pigments due to the presence of purslane in their composition. This agrees with other investigations which mentioned that purslane has an elevated content of alpha and beta chlorophylls (Nurfaizah et al, 2015). Our results showed that foliage from OP1 samples is a good source of photosynthetic pigments; in addition, the proportion of carotenoids that OP1 contains are similar to other food supplements.…”
Section: Antioxidant Compoundssupporting
confidence: 92%